ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN DENGAN CITRA MEREK SEBAGAI VARIABEL INTERVENING (STUDI PADA PENGGUNA SMARTPHONE XIAOMI DI UNIVERSITAS DIPONEGORO) - Aprinuryanto, Naufal Afiqusholih; Santosa, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2019)
Communication tool is one of the needs that is not less important in human life.One type of communication tool that is often used at this time is a smartphone. in thepurchase decision of a product, a buyer must find out about the product. such as pricefactors, product benefits, product brands and the experience of others about the product.The purpose of this research is to analyze the influence of price perception, product qualityand word of mouth against purchasing decision with the brand image as an interveningvariable.The research was conducted for students of Diponegoro University. The samples inthis research as much as 150 respondents. With the method of collecting data throughquestionnaries and sampling method in this research is non probability sampling withpurposive sampling technique. This research examines the hypothesis by using StructuralEquation Modeling (SEM).The results of this study shows that price perception has positive and significanteffect on brand image, product quality has positive and significant effect on brand image,word of mouth has positive and significant effect on brand image. It is also known thatbrand image is proven to mediate price, product quality and word of mouth on purchasingdecision.